2-Deoxy-d-Glucose Treatment Decreases Anti-inflammatory M2 Macrophage Polarization in Mice with Tumor and Allergic Airway Inflammation - Zhao, Qingjie; Chu, Zhulang; Zhu, Linnan; Yang, Tao; Wang, Peng; Liu, Fang; Huang, Ying; Zhang, Fang; Zhang, Xiaodong; Ding, Wenjun; Zhao, Yong (Frontiers in Immunology, 2017)
As important effector cells in inflammation, macrophages can be functionally polarized into either inflammatory M1 or alternatively activated anti-inflammatory M2 phenotype depending on surroundings. The key roles of glycolysis in M1 macrophage polarization have been well defined. However, the relationship between glycolysis and M2 polarized macrophages is still poorly understood. Here, we report that 2-deoxy-d-glucose (2-DG), an inhibitor of the glycolytic pathway, markedly inhibited the expressions of Arg, Ym-1, Fizz1, and CD206 molecules, the hall-markers for M2 macrophages, during macrophages were stimulated with interleukin 4. The impacted M2 macrophage polarization by 2-DG is not due to cell death but caused by the impaired cellular glycolysis. Molecular mechanism studies indicate that the effect of 2-DG on M2 polarized macrophages relies on AMPK-Hif-1α-dependent pathways. Importantly, 2-DG treatment significantly decreases anti-inflammatory M2 macrophage polarization and prevents disease progression in a series of mouse models with chitin administration, tumor, and allergic airway inflammation. Thus, the identification of the master role of glycolysis in M2 macrophage polarization offers potential molecular targets for M2 macrophages-mediated diseases. 2-DG therapy may have beneficial effects in patients with tumors or allergic airway inflammation by its negative regulation on M2 macrophage polarization.